Synthesis, Anti-Cancer and Anti-HIV Activities of Some New Formazans - Bhardwaj, S.D. (Asian Journal of Chemistry, 2010)
A series of 1-phenyl-3-(2-methoxy-4-N,N'-bis-2-cyanoethylaminophenyl)2-hydroxy-5-bromobenzoformazan have been synthesisedby reacting 2-methoxy-4-N,N'-bis-2'-cyanoethylaminobenzaldehyde with 5-bromosalicyl-hydrazide which gaverespective acid hydrazone. The acid hydrazone on reaction withdiazotized aromaticamines furnished formazans in good yield.